Pemanfaatan Media TikTok Akun @Rosiii____ Dalam Menunjukan Sikap Kepercayaan Diri Remaja Putri IKRA GSP - aulia nuraziza; Ayu Nur Faadiyah; Nabilah (Komsospol, 2026)
This research aims to investigate the use of the TikTok account @rossiii____ to demonstrate self-confidence among young women in the IKRA GSP community, and further, to identify the motives and gratifications they derive from consuming this specific media content. TikTok has rapidly become a dominant global social media platform, with content creators like @rossiii____, who specialize in clothing and fashion ideas, significantly shaping young people's choices and public self-expression. In this research employs an Interpretative Paradigm and employs a Descriptive Qualitative Approach with a Case Study design. Data collection was conducted systematically through observations of community members, in-depth interviews with key informants from young women in IKRA GSP, and careful documentation of TikTok content. This study is theoretically grounded in Uses and Gratifications Theory, analyzing findings based on audience motives (Information, Personal Identity, Social Integration, and Entertainment) and the resulting gratifications. This analysis critically links the use of this media to three components of self-esteem: cognitive (acquisition of knowledge about wardrobe coordination), affective (generation of positive feelings and motivation), and conative (behavioral actions in implementing new styles). This study is expected to provide a comprehensive framework for understanding how very specific social media content is actively sought and used by young women to fulfill their needs for expression and increase their selfesteem, enriching the application of Uses and Gratifications Theory in the digital fashion influence landscape.